Reinstatement of Eutrombicula butantanensis (Fonseca, 1932) (Trombidiformes: Trombiculidae) - Silva, Ricardo Bassini [UNESP] (2022)
Eutrombicula Ewing is currently represented with more than 80 species worldwide parasitizing amphibians, reptiles, birds, and mammals. In the present study, we examined the type series and additional material of two Neotropical chigger’s species: Eutrombicula butantanensis (Fonseca) and E. ophidica (Fonseca). Eutrombicula butantanensis (Fonseca) was previously synonymized with E. alfreddugesi (Oudemans). However, we are proposing the reinstatement of E. butantanensis as a valid species. Besides that, we are proposing that E. ophidica is a junior synonym of E. butantanensis. Beyond the morphological similarities, E. butantanensis and E. ophidica were initially described to the state of São Paulo, Brazil, and were accidentally collected parasitizing the skin of a human. Besides that, we are increasing the knowledge about E. butantanensis on Brazil’s national territory, recording new locality and host associations.